Point-of-Care Testing for Multiple Cardiac Markers Based on a Snail-Shaped Microfluidic Chip - Yin, Binfeng; Wan, Xinhua; Qian, Changcheng; Sohan, A. S. M. Muhtasim Fuad; Wang, Songbai; Zhou, Teng (Frontiers in Chemistry, 2021)
Existing methods for detecting cardiac markers are difficult to be applied in point-of-care testing (POCT) due to complex operation, long time consumption, and low sensitivity. Here we report a snail-shaped microfluidic chip (SMC) for the multiplex detection of cTnI, CK-MB, and Myo with high sensitivity and short detection time. The SMC consists of a sandwich structure: a channel layer with the mixer and reaction zone, a reaction layer coated with capture antibodies, and a base layer. The opening or closing of the microchannels is realized by controlling the downward movement of the press-type mechanical valve. The chemiluminescence method was used as a signal readout, and the experimental conditions were optimized. SMC could detect cTnI, CK-MB, Myo at concentrations as low as 1.02 pg/mL, 1.37 pg/mL, 4.15 pg/mL. The SMC will be a promising platform for simultaneous determination of multianalyte and shows a potential application in POCT.